Emerging roles of PtdIns(4,5)P(2) – beyond the plasma membrane - Tan, Xiaojun (J Cell Sci, 2015)
Phosphoinositides are a collection of lipid messengers that regulate most subcellular processes. Amongst the seven phosphoinositide species, the roles for phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P(2)] at the plasma membrane, such as in endocytosis, exocytosis, actin polymerization and focal adhesion assembly, have been extensively studied. Recent studies have argued for the existence of PtdIns(4,5)P(2) at multiple intracellular compartments, including the nucleus, endosomes, lysosomes, autolysosomes, autophagic precursor membranes, ER, mitochondria and the Golgi complex. Although the generation, regulation and functions of PtdIns(4,5)P(2) are less well-defined in most other intracellular compartments, accumulating evidence demonstrates crucial roles for PtdIns(4,5)P(2) in endolysosomal trafficking, endosomal recycling, as well as autophagosomal pathways, which are the focus of this Commentary. We summarize and discuss how phosphatidylinositol phosphate kinases, PtdIns(4,5)P(2) and PtdIns(4,5)P(2)-effectors regulate these intracellular protein and membrane trafficking events.